ANSIEDADE DE PROVA EM JOVENS: UMA ANÁLISE A PARTIR DOS TRAÇOS DE PERSONALIDADE E DA MOTIVAÇÃO ACADÊMICA - Gabriel, Rose Skripka do Nascimento (2019)
This study aimed to analyze the possible relationships between test anxiety, personality traits, and academic motivation of adolescents aged 11 to 17 years. A literature review was conducted on the main theoretical assumptions and state of the art about anxiety, test anxiety, personality traits, and academic motivation. Motivation has been studied in the light of self-determination theory, which spells out motivation on a continuum from demotivation and extrinsically motivated regulation to intrinsic motivation, associated with self-determined behavior. The personality traits have been researched upon Hans Eysenck's psychophysiological perspective, defined as neuroticism, extroversion, and psychoticism. To measure the constructs, three already validated scales were used: Test Anxiety Inventory, which measures the dimensions worry, emotion, distraction, and confidence; Academic Motivation Scale, which encompasses the types of motivation; and the EPQ-J, a questionnaire that measures personality traits in adolescents. Data were collected from a convenience sample of 210 young students aged 11 to 17 (Mage = 13.54; SD = 1.85), 56.7% female, from two public schools and one private school in Sao Paulo city. Four hypothetical models were formulated. The dimensions of the test anxiety were defined as dependent variables and the dimensions of personality traits and academic motivation were the predictor variables. The technique chosen for data analysis was stepwise multiple regression. The results showed that: the group of independent variables (IVs) responsible for 33% in the variation of the dependent variable (DV) worry was composed of neuroticism, external regulation motivation, identified motivation, and intrinsic motivation, presenting an effect size (f2) of 0.501. The group of IVs responsible for 34% in the variation in DV emotion was composed of neuroticism and external motivation, with f2 = 0.512. The group of IVs responsible for 26% of the variation in DV distraction was composed of external motivation, neuroticism and introjected motivation, with f2 = 0.351. The group of IVs responsible for 32% of the variation in DV confidence was composed of neuroticism and intrinsic motivation, with f2 = 0.468. Among the formulated relationships, the following stand out: the prevalence of the neuroticism trait and external motivation as predictors of test anxiety, the positive relationship between intrinsic motivation and confidence, and the negative relationship between intrinsic motivation and worry.